Vaccine Cold Chain Management at Puskesmas Level in Semarang City - Dian Nintyasari Mustika; Sherkia Ichtiarsi Prakasiwi (Universitas Muhammadiyah Semarang, 2022)
At present, measles is the biggest cause of child mortality among other diseases that can be prevented by immunization. Vaccines are biological elements that have certain characteristics and require special cold chain handling of vaccines since they are produced at the factory until they are used in service units. With the wrong method of storing vaccines, it can cause damage to the vaccine causing AEFI (Post Immunization Adverse Events). Cold chain procedures must be managed properly by keeping vaccines within the recommended temperature range from the transport stage to vaccine storage. The purpose of this study was to determine how the vaccine cold chain is managed at the puskesmas level in the city of Semarang. The design of this research is cross sectional. The samples in this study were vaccine management officers and vaccine storage facilities. The sampling technique in this study was simple random. The sample size is 5 health centers in the city of Semarang. The data was collected by interviewing the puskesmas officers and observing the vaccine storage facilities at the puskesmas. From the results of the study, it was found that there were more respondents who had never received cold chain management training than those who had attended training. To increase the knowledge and skills of immunization officers, it is necessary to conduct training in accordance with the training module for immunization officers.